COSTING AND TARIFFS ON COMMUTER RAIL OF PASSENGER TRANSPORTATION - Balaka, Ye. I.; Sementseva, O. V.; Vasyliev, O. L. (Science and Transport Progress, 2007)
Untraditional for railway transport approach to calculation of suburban passenger transportations prime cost, tariff definition and on its basis the cost of transportations on different distance in trains that differ by account of passenger and sections are proposed.